EVALUASI PENGENDALIAN INTERN PADA SISTEM PEMBELIAN BAHAN BAKU (Studi pada PT. Fifatex Pekalongan, Jawa Tengah) - Poltak Sianipar (Jurnal Administrasi Bisnis, 2015)
The application of internal control was needed to run the company activities. In this research activities buy raw materials required to meet the needs of company. The application of Internal control on activities at the purchase of raw materials was undertaken to reduce fraud that could happen as geminating function and a shortage of other in the process of the purchase of raw materials done by the company. This study attempts to know and to evaluate the application of internal control on a system purchases of raw materials in PT.Fifatex Pekalongan. The results of the study can be seen that the application of internal control on the buying system was less well with there are still geminating function and lack of a document that supports receipt of the goods. Audits of internal control on the structure of organization to an enterprise and a division of labor in this company was less than satisfactory seen from geminating function on the purchase and the finance division. Applied to the use of internal control document in the company still less good then need the addition of a document that can help smooth the activities of the purchase in the company . Keywords : The Application, Document, Activities Abstrak Penerapan pengendalian intern sangat diperlukan dalam menjalankan kegiatan perusahaan. Pada penelitian ini kegiatan pembelian bahan baku diperlukan untuk memenuhi kebutuhan perusahaan. Penerapan Pengendalian intern pada kegiatan pembelian bahan baku dilaksanakan untuk mengurangi kecurangan yang bisa terjadi seperti perangkapan fungsi dan kekurangan lainnya didalam proses pembelian bahan baku yang dilakukan oleh perusahaan. Penelitian ini bertujuan untuk mengetahui dan mengevaluasi penerapan pengendalian intern pada sistem pembelian bahan baku di PT. Fifatex Pekalongan. Hasil penelitian dapat diketahui bahwa penerapan pengendalian intern pada sistem pembelian masih kurang baik dengan masih ada perangkapan fungsi dan kurangnya dokumen yang mendukung penerimaan barang. Pengendalian intern pada struktur organisasi perusahaan dan pembagian tugas pada             PT. Fifatex masih kurang baik dilihat dari perangkapan fungsi pada bagian pembelian dan bagian keuangan. Pengendalian intern yang diterapkan pada penggunaan dokumen dalam perusahaan masih kurang baik maka perlu adanya tambahan sebuah dokumen yang dapat membantu kelancaran kegiatan pembelian dalam perusahaan. Kata Kunci : Penerapan, Dokumen, Kegiatan